2022
DOI: 10.11591/eei.v11i4.3290
|View full text |Cite
|
Sign up to set email alerts
|

Classification of covid patient image dataset using modified deep convolutional neural network system

Abstract: The number of people infected with the corona virus is steadily rising. Even after being treated and returned to normality, many who were impacted are still suffering from a variety of health problems. We suggest a new, more effective approach to dealing with this issue, as well as putting in place preventative measures to prevent the spread of disease. The modified convolutional neural networks (M-CNN) architecture is modified deepCNN architecture. Using existingcorona virus disease 2019(COVID-19) computerize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Because of the absence of significant conservation markers within their sequencing, automatic recognition of fRNAs using genomic patterns was not as reliable as recognition of protein-coding RNAs. Which were exceptionally trustworthy based on analytical and technological evaluations, it provided a computerized analysis of the genomes for T. brucei and L. braziliensis in the hopes of discovering a group of preserved ncRNAs.We showed that this technique could identify a significant variety of possible ncRNAs, both identified and unknown [10][11].We look at possible Premi RNAs within prospective ncRNAs and find that the occurrence of miRNA sequences maintained across T. brucei and L. braziliensis was very improbable. We also employ a new strategy for identifying shorter regulation RNA motifs in T.brucei genomes' 5' & 3' UTRs, which are homology-independent [12][13].…”
Section: Related Workmentioning
confidence: 97%
“…Because of the absence of significant conservation markers within their sequencing, automatic recognition of fRNAs using genomic patterns was not as reliable as recognition of protein-coding RNAs. Which were exceptionally trustworthy based on analytical and technological evaluations, it provided a computerized analysis of the genomes for T. brucei and L. braziliensis in the hopes of discovering a group of preserved ncRNAs.We showed that this technique could identify a significant variety of possible ncRNAs, both identified and unknown [10][11].We look at possible Premi RNAs within prospective ncRNAs and find that the occurrence of miRNA sequences maintained across T. brucei and L. braziliensis was very improbable. We also employ a new strategy for identifying shorter regulation RNA motifs in T.brucei genomes' 5' & 3' UTRs, which are homology-independent [12][13].…”
Section: Related Workmentioning
confidence: 97%
“…The proposed intrusion detection system, which is based on a neural network model, manages healthcare information and ensures that healthcare providers' jobs are completed effectively. The proposed system effectively manages data for all clinical, financial, research lab, outpatient care, primary care, operating room, equipment, nursing, pharmacy, radiation oncology, pathology, and other departments of healthcare [21].…”
Section: Introductionmentioning
confidence: 99%
“…The system comprises of a GSM module and Arduino controller, a set of sensors, and a mobile app or website that can be used to monitor and records the data. The wireless link between the sensors and the mobile application is created via the GSM module [15][16]. The mobile application receives the processed data from the Arduino controller after it has been sent from the sensors.…”
Section: Introductionmentioning
confidence: 99%